Pedagogy and Psychology as the Sciences of Forming the Potential of Modern Society - Shchedrina E. V., Matasova I. I., Panchenko I. V., Statsenko O. V., Gordeeva K. D., Nikolaev A. V., Sadovnikov N. V., Sadovnikov N. V., Shipanova E. V., Shipanova E. V., Sultanova G. A., Sultanova G. A., Kovalenko S. V., Sazonova L. A., Eremeeva O. V., Agibalova A. A., Ustimenko O. A., Zenkina V. G., Sudakov D. V., Sudakov O. V., Iakusheva N. V., Shevtsov A. N., Belov E. V., Ambartsumian N. A., Kostenko E. G., Usoltseva V. V. (Pedagogy and Psychology as the Sciences of Forming the Potential of Modern Society, 2021)
the article reveals the relationship between the principles of fundamentality and the military-professional orientation of studying the elements of mathematical logic in a military university. An unconventional approach to the study of this course is proposed, which is based on a functional approach that gives a more general idea of the elements of mathematical logic.
Keywords: фундаментализация подготовки военного инженера; профессионально-военная направленность обучении курсантов; двузначная логика; бесконечнозначная логика; порядковая логика; булевы функции; канонические формы булевых функций: СДНФ и СКНФ; минимизация булевых функций; простые импликанты; алгоритм Квайна получения сокращенной ДНФ булевых функций; fundamentalization of military engineer training; professional-military orientation of cadet training; two-digit logic; infinite-value logic; ordinal logic; boolean functions; canonical forms of boolean functions: SDNF and SKNF; minimization of boolean functions; simple implicants; Quine's algorithm for obtaining abbreviated DNF of boolean functions